Spectrophotometric Characterization of Doped Pr(III) Ion in Saturated Aqueous Solutions of Some Pharmaceutical Compounds - Naulakha, Neelam; Soni, K.P.; Bhati, P.R.; Joshi, G.K. (Asian Journal of Chemistry, 2010)
The stereo-environment of doped Pr(III) ion in saturated solution of some pharmaceutical organic compounds in aqueous media has been discussed on the basis of various electronic spectral parameters. The various electronic parameters, viz., Judd-Ofelt intensity parameter, Tλ, Slater-Condon (Fk), Lande's (ζ4f) intensity of hypersensitive band (3P2) and Racah's (Ek) as well as bonding parameter b½ for Pr(III) ion doped in aqueous saturated solution of diphenhydramine, tripelennamine, chlorphenaramine, promethazine, terfinadine, naproxen, fenoprofen, flurbiprofen, oxaprozin, ketoprofen and ibuprofen.